MANAJEMEN PEMBELAJARAN KEWIRAUSAHAAN DENGAN PENDEKATAN OPEN-ENDED UNTUK MEMBANGUN BERPIKIR KREATIF SISWA SMK - Indah Surya Wardani (UNIVERSITAS BENGKULU, 2016)
This study aims to describe the steps of learning management approach that builds open-ended creative thinking math class X SMK Negeri 2 Bengkulu City. This study used a qualitative approach with classroom action research (PTK) as a kind of research. The subjects of this study 25 students. The data collected in this study includes data process and outcome data. Data collection instruments include observation sheet activities of teachers and students, a test sheet, the interview format, and documentation that includes Learning Implementation Plan, Student Worksheet, and documentation of learning in the classroom (photo). There are seven steps in the learning of the open -ended approach that builds creative thinking.Keywords: learning, open-ended, creative thinking